1999
DOI: 10.1016/s0014-5793(99)00587-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel anti‐hypertensive peptide derived from ovalbumin induces nitric oxide‐mediated vasorelaxation in an isolated SHR mesenteric artery

Abstract: In this report, we deal with the isolation of a novel vasorelaxing peptide from a chymotryptic digest of ovalbumin and its vasorelaxing activities. This peptide is composed of ArgAla-Asp-His-Pro-Phe (RADHPF) in its sequence, corresponding to residues 359^364 of ovalbumin. This peptide (30^300 W WM) exerted a dose-dependent vasodilation in an isolated mesenteric artery from a spontaneously hypertensive rat which was preconstricted by phenylephrine, besides the relaxation being endothelium-dependent. It is notew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 14 publications
5
75
0
Order By: Relevance
“…It is noteworthy that NO is regarded as an important signaling molecule in vasodilation, neurotransmission, and host immune defense (Ahn et al, 2012) and peptides from whey protein (Ballard et al, 2009), Aa-lactabumin and Ab-lactabumin (Sipola et al, 2002), ovalbumin (Matoba et al, 1999), flaxseed protein (Udenigwe and Aluko, 2012), skeletal muscle protein (Takahashi et al, 2009), and even human casein (Fujita et al, 1996) were found to enhance NO production.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…It is noteworthy that NO is regarded as an important signaling molecule in vasodilation, neurotransmission, and host immune defense (Ahn et al, 2012) and peptides from whey protein (Ballard et al, 2009), Aa-lactabumin and Ab-lactabumin (Sipola et al, 2002), ovalbumin (Matoba et al, 1999), flaxseed protein (Udenigwe and Aluko, 2012), skeletal muscle protein (Takahashi et al, 2009), and even human casein (Fujita et al, 1996) were found to enhance NO production.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…A number of bioactive peptides derived from the enzymatic digestion of food proteins exhibit various physiological functions, including antihypertensive (Matoba et al, 1999;Zhao, et al, 2008) and cholesterol-lowering (Yamauchi, et al, 2003) activities. et al (2011) showed that soymorphin-5, a pentapeptide derived from the β-subunit of βCG, improves glucose and lipid metabolism in KK-A y mice, probably via activation of the adiponectin and PPARγ pathways, followed by increases in β-oxidation and energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…A vasorelaxing peptide -ovokinin (2-7) -was isolated from chymotryptic digest of ovalbumin [87]. However, the mechanisms for the relaxation were different from ovokinin.…”
Section: Ovoalbumin Peptide (Ovokinin)mentioning
confidence: 99%